Ethylene Response Factor109 Attunes Immunity, Photosynthesis, and Iron Homeostasis in Arabidopsis Leaves - Yang, Chiu-Ling; Huang, Yu-Ting; Schmidt, Wolfgang; Klein, Patricia; Chan, Ming-Tsair; Pan, I-Chun (Frontiers in Plant Science, 2022)
Iron (Fe) is an essential micronutrient element for all organisms including plants. Chlorosis of young leaves is a common symptom of Fe deficiency, reducing the efficiency of photosynthesis, and, ultimately, crop yield. Previous research revealed strong responsiveness of the putative key transcription factor ERF109 to the Fe regimen. To elucidate the possible role of ERF109 in leaf Fe homeostasis and photosynthesis, we subjected Arabidopsis thaliana erf109 knockout lines and Col-0 wild-type to transcriptome profiling via RNA-seq. The transcriptome profile of Fe-sufficient erf109 leaves showed a 71% overlap with iron deficiency Col-0 plants; the differential genes expressed in Fe deficiency Col-0 plants were largely abolished in erf109 genotypes under conditions of Fe deficiency. Moreover, mutations in ERF109 led to significant down-regulation of defense genes, including CML37, WRKY40, ERF13, and EXO70B2. Leaves of erf109 exhibited increased Fe concentrations under both Fe-sufficient and Fe-deficient conditions. Reduced Fv/Fm and SPAD values of erf109 lines under Fe deficiency indicates curtailed ability of photosynthesis relative to the wild type. Our findings suggest that ERF109 is a negative regulator of the leaf response to Fe deficiency. It appears that the function of ERF109 in the Fe response is critical for regulating pathogen defense and photosynthetic efficiency. Taken together, our study reveals a novel function of ERF109 and provides a systematic perspective on the intertwining of the immunity regulatory network and cellular Fe homeostasis.